Association between body mass index and return to work following primary knee arthroplasty: a population-based cohort study on 6,128 patients from Danish national registers - Julie B Pajaniaye; Peter Alsing; Martin G Stisen; Erzsébet Horváth-Puhó; Maaike G J Gademan; Alma B Pedersen; Inger MECHLENBURG Mechlenburg (Acta Orthopaedica)
Background and purpose: With more knee arthroplasties (KAs) performed in working-age patients, interest in return to work (RTW) increases. We aimed to investigate the association between body mass index (BMI) and RTW after primary KA and whether the association varies by sex, age, comorbidity, and socioeconomic position. Methods: From Danish national registries, we included 6,128 patients aged 18 to 60 years undergoing KA from 2008–2018. Exposure was BMI in categories < 25.0, 25.0–29.9, 30.0–34.9, 35.0–39.9, and ≥ 40.0. Outcome was RTW after KA. We estimated cumulative incidence proportions (CIP) of RTW. Cox regression was used to calculate hazard ratios (HRs) with 95% confidence intervals (CI). Results: Median time to RTW was 70 days. Overall CIP for RTW was 63% (CI 62–65) at 3 months. With BMI < 25 as reference, CIP was 65% (n = 1,401) for BMI 25.0–29.9, 64% (n = 1,130) for BMI 30.0–34.9, 60% (n = 528) for BMI 35.0–39.9, and 60% (n = 260) for BMI ≥ 40.0, corresponding to an adjusted HR of 1.06 (CI 0.98–1.15), 1.02 (CI 0.94–1.11), 0.97 (CI 0.88–1.06), and 0.96 (CI 0.85–1.08). Men with BMI 35.0–39.9 and ≥ 40 had an adjusted HR of 0.89 (CI 0.76–1.05) and 0.87 (CI 0.70–1.10). None of the associations were statistically significant. Age, comorbidity, and socioeconomic position did not modify the association between BMI and RTW. Conclusion: More than 60% of patients RTW within 3 months but we found no association between BMI and RTW after primary KA.